Soluble ST2 concentrations associate with in-hospital mortality and need for mechanical ventilation in unselected patients with COVID-19. Issue 2 (21st December 2021) - Omland, Torbjorn; Prebensen, Christian; Jonassen, Christine; Svensson, My; Berdal, Jan Erik; Seljeflot, Ingebjørg; Myhre, Peder Langeland
Abstract : Objective: Soluble ST2 (sST2) reflects inflammation, endothelial dysfunction and myocardial fibrosis, is produced in the lungs and is an established biomarker in heart failure. We sought to determine the role of sST2 in COVID-19 by assessing pathophysiological correlates and its association to in-hospital outcomes. Methods: We enrolled 123 consecutive, hospitalised patients with COVID-19 in the prospective, observational COVID-19 MECH study. Biobank samples were collected at baseline, day 3 and day 9. The key exposure variable was sST2, and the outcome was ICU treatment with mechanical ventilation or in-hospital death. Results: Concentrations of sST2 at baseline was median 48 (IQR 37–67) ng/mL, and 74% had elevated concentrations (>37.9 ng/mL). Higher baseline sST2 concentrations were associated with older age, male sex, white race, smoking, diabetes, hypertension and chronic kidney disease. Baseline sST2 also associated with the presence of SARS-CoV-2 viraemia, lower oxygen saturation, higher respiratory rate and increasing concentrations of biomarkers reflecting inflammation, thrombosis and cardiovascular disease. During the hospitalisation, 8 (7%) patients died and 27 (22%) survivors received intensive care unit (ICU) treatment. Baseline sST2 concentrations demonstrated a graded association with disease severity (median, IQR): medical ward 43 (36–59) ng/mL; ICU 67 (39–104) ng/mL and non-survivors 107 (72–116) ng/mL (p<0.001 for all comparisons). These associations persisted at day 3 and day 9 . Conclusions: sST2 concentrations associate with SARS-CoV-2 viraemia, hypoxaemia and concentrations of inflammatory and cardiovascular biomarkers. There was a robust association between baseline sST2 and disease severity that was independent of, and superior to, established risk factors. sST2 reflects key pathophysiology and may be a promising biomarker in COVID-19. Trial registration number: NCT04314232 .